The effects of frequency lowering on speech perception in noise with adult hearing-aid users. (3rd May 2016) - Miller, Christi W.; Bates, Emily; Brennan, Marc
Abstract: Objective : Frequency lowering (FL) strategies move high frequency sound into a lower frequency range. This study determined if speech perception differences are observed between some of the different frequency lowering strategies that are available. Design : A cross-sectional, repeated-measures design was used to compare three hearing aids that used wide-dynamic range compression (WDRC) and either non-linear frequency compression (NFC), linear frequency transposition (LFT), or frequency translation (FT). The hearing aids were matched to prescriptive real ear targets for WDRC. The settings for each FL strategy were adjusted to provide audibility for a 6300 Hz filtered speech signal. Sentence recognition in noise, subjective measures of sound quality, and a modified version of the speech intelligibility index (SII) were measured. Study sample : Ten adults between the ages of 63 to 82 years with bilateral, high frequency hearing loss. Results : LFT and FT led to poorer sentence recognition compared to WDRC for most individuals. No difference in sentence recognition occurred with and without NFC. The quality questionnaire and SII showed few differences between conditions. Conclusion : Under similar fitting and testing conditions of this study, FL techniques may not provide speech understanding benefit in certain background noise situations.